Karakteristik pengelolaan keuangan rumah tangga baru di era pandemi - Fitriana Santi; Ary Yunita Anggraeni (Universitas Pamulang, 2021)
The covid 19 outbreak that hit Indonesia had a significant impact on the country's economy and the economy of a family. The existence of several governments tightened regulations ranging from PSBB (Large-Scale Social Restrictions) to PPKM (Enforcement of Restrictions on Community Activities) in an emergency has created a commotion in the economy of young couples. Prosperous families can manage finances well so that family goals can be achieved. In young couples, many of them were shaken by this pandemic. Therefore, researchers conducted a study to know the characteristics of new household financial management in the Pandemic Era. This research uses qualitative research with a phenomenological approach. The data is taken by interview technique by the informant who has been selected according to the criteria. The study results show that young couples in financial planning will sort according to the priority scale of needs: daily needs, children's education funds, emergency funds, savings, debt installments, and entertainment AbstrakWabah Covid 19 yang melanda Indonesia nyatanya memberikan pengaruh besar tidak hanya pada perekonomian negara melainkan juga perekonomian suatu keluarga. Adanya beberapa aturan yang diperketat oleh pemerintah mulai dari PSBB (Pembatasan Sosial Berskala Besar) sampai dengan PPKM (Pemberlakukan Pembatasan Kegiatan Masyarakat) secara darurat cenderung mengganggu ekonomi pasangan muda. Keluarga sejahtera merupakan mereka yang mampu mengelola keuangan dengan baik sehingga tercapainya tujuan berkeluarga. Tidak sedikit keluarga pasangan muda terguncang akibat pandemi. Oleh karena itu, peneliti termotivasi untuk menelaah karakteristik pengelolaan keuangan rumah tangga baru di Era Pandemi. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan fenomenologi. Data diambil dengan teknik wawancara dari informan yang telah dipilih sesuai dengan kriteria. Hasil penelitian ini menujukkan bahwa pasangan muda akan melakukan perencanaan keuangan dengan mengurutkan skala prioritas kebutuhan yakni: kebutuhan sehari-hari, dana pendidikan anak, dana darurat, tabungan, cicilan hutang dan hiburan